Arsenic (As) contamination in sediments from coastal areas of China. (February 2022) - Liu, Xun; Zeng, Biao; Lin, Guo
Abstract: Arsenic (As) from various anthropogenic sources has accumulated in estuarine and coastal sediments of China in the past decade, but we know little about the overall situation of As pollution at a national scale. Here, we analysed the spatial-temporal distribution characteristics, source, fate, and potential risks of As from 11 provincial-level regions across coastal China based on reviewed data extracted from previous studies published in the past 20 years. The anthropogenic contribution to As load was evident in 8 out of 11 provinces, especially in developed areas such as Tianjin, Zhejiang, and Guangdong. The weighted mean concentration of As in coastal sediments was 9.75 mg kg −1, which was close to national agricultural land (10.7 mg kg −1 ) and mixed land (12.1 mg kg −1 ) soil values, and this indicated the likely terrestrial influences and homogenization of As distribution at the interface between land and sea. The accumulation has decreased significantly since 2005, which might be due to continuously reduced emissions from farming and animal husbandry and household consumption in the catchment of coastal areas. The geoaccumulation index indicated that the proportions of unpolluted, unpolluted to moderately polluted, and moderately polluted cases were 48%, 28%, and 8%, respectively. This study provides a comprehensive and quantitative review on As contamination in coastal sediments on a national scale. The results could be used in coastal sediment quality assessment and decision-making by authorities to meet the regulatory requirements linked to coastal environmental protection and management. Graphical abstract: Unlabelled Image